The Development of Early Childhood Naturalist Intelligence through Environmental Education - Priadi, Agus; Fatria, Erian (Program Studi Magister Pendidikan Anak Usia Dini, 2024)
Environmental education exists as a solution to improving the intelligence of early childhood naturalists, but its implementation is often forgotten or only as a hidden curriculum. The purpose of this study is to provide information related to the implementation of environmental education for early childhood to improve the intelligence of early childhood naturalists. The research method used in this study is a qualitative method presented in the form of an in-depth literature review. Literature study efforts are carried out by reading, observing, recognizing, and describing to analyze reading material in the form of related literature as a reference source. The result of this study is that the use of instructional strategies for gardening activities and creative game-based environmental learning can be considered to improve the intelligence of early childhood naturalists. In addition, it was also found that the material often used by educators to improve naturalist intelligence is the introduction of animals and plants. The trend of measuring the intelligence of early childhood naturalists uses many observation sheets, but it is also recommended to use research instruments that have been standardized or published in reputable scientific articles to obtain valid and reliable data. Keywords: environmental education, early childhood, naturalist intelligence References: Adawiyah, A. S. R., &; Dewinggih, T. (2021). Environmental Education in Early Childhood through the provision of trash cans and simulation methods. Proceedings UIN Sunan Gunung Djati Bandung, 1(November), 12–23. https://proceedings.uinsgd.ac.id/index.php/Proceedings Adawiyah, R., Rohyana, F., &; Ashari, M. A. (2019). Development of Naturalist Intelligence through Science-based Project Methods at TK Titipan ilahii rencoong Kelayu Jorong. CARE Journal, 7(1), 1–6. https://core.ac.uk/download/pdf/229499766.pdf Agustiana, M. (2021). Efforts to Improve Early Childhood Naturalistic Intelligence of 5-6 Years through Farming Activities at Tk PGRI Bandar Lampung [Raden Intan State Islamic University Lampung]. http://repository.radenintan.ac.id/15122/ Amini, R., &; Munandar, A. (2014). The influence of the outdoor-based environmental education learning model on mastery of the concept of environmental education for prospective elementary school teachers. Journal of Educational Research, 11(1), 14–21. http://www.jurnal.upi.edu/file/3_risda.pdf Anggraini, D. (2017). Improve the naturalist intelligence of children aged 5-6 years through plant exploration. Yaa Bunayya: Journal of Early Childhood Education, 1(2), 137–146. https://doi.org/https://doi.org/10.24853/yby.1.2.137-146 Aprilianti, R., &; Septiani, S. (2021). Improve the naturalist intelligence of children aged 5-6 years through a scientific approach. Golden Age Journal, Hamzanwadi University, 5(02), 393–407. https://doi.org/https://doi.org/10.29408/jga.v5i02.3962 Ardoin, N. M., &; Bowers, A. W. (2020). Early childhood environmental education: A systematic review of the research literature. Educational Research Review, 31(November 2019), 100353. https://doi.org/10.1016/j.edurev.2020.100353 Asih, S., &; Susanto, A. (2017). Increasing naturalist intelligence in children aged 5-6 years through learning models in natural material centers. Yaa Bunayya : Journal of Early Childhood Education, 1(1), 33–38. https://doi.org/https://doi.org/10.24853/yby.1.1.33-38 Chandrawati, T. (2021). ECCE teachers' understanding of environmental literacy is related to environmental education. Proceedings of Covid 19 Era Integrative Holistic Early Childhood Development, September, 125–130. https://ejurnal.pps.ung.ac.id/index.php/paudhi/article/view/897 Cinantya, C., &; Maimunah. (2022). Science Learning Based on Creative Play Activities in Wetland Environments to Develop Early Childhood Naturalistic Intelligence. Journal of Early Childhood Education Undiksha, 10(3), 449–456. https://doi.org/https://doi.org/10.23887/paud.v10i3.52560 Creswell W., J. (2013). Research Design Qualitative, Quantitative, and Mixed Approaches. Learning Library. Destarani, A., &; Sari, R. N. (2021). Naturalist Intelligence in PAUD SPS An-Nabat Class A. Journal of Madrasah Ibtidaiyah Teacher Education, 01(01), 1–6. https://doi.org/https://doi.org/10.54892/jpgmi.v1i1.127 Devi Artanti, G., Fidesrinur, F., &; Garzia, M. (2022). Stunting and Factors Affecting Toddlers in Indonesia. JPUD - Journal of Early Childhood Education, 16(1), 172–185. https://doi.org/10.21009/jpud.161.12 Djoehaeni, H. (2014). Learning Model of Environmental Education in Early Childhood Education. Edutech, 13(1), 1. https://doi.org/10.17509/edutech.v13i1.3216 Dwikayani, Y. (2015). IMPROVE CHILDREN'S NATURALIST INTELLIGENCE THROUGH GARDENING ACTIVITIES. Growth and Development : A Study of ECCE Theory and Learning, 5(01). https://doi.org/https://doi.org/10.36706/jtk.v5i1.8202 Ekayanti, Y. (2014). Developing naturalist intelligence about the preschool environment of children aged 5-6 years Tk Lkia III Pontianak. Journal of Equatorial Education and Learning, 3(3), 1–13. https://doi.org/https://dx.doi.org/10.26418/jppk.v3i3.5003 Fajrin, L. P. (2020). Environmental Education in Raudhatul Athfal. Journal of Tunas Siliwangi, 6(2), 71–77. https://doi.org/https://doi.org/10.22460/ts.v6i2p71-77.2080 Fajrin, L. P., &; Alwiyah, N. (2023). Implementation of Naturalist Intelligence Development in Early Childhood Aisyiyah Kindergarten Kartasura Branch. Journal of Shoots, 9(1), 8–16. https://doi.org/https://doi.org/10.22460/ts.v9i1.3387 Fang, W.-T., Hassan, A., &; LePage, B. A. (2022). The Living Environmental Education. Springer Nature. https://doi.org/10.1007/978-981-19-4234-1 Fatria, E. (2023). Differences in student knowledge about the health of public places and tourism using project based learning strategies and strategies. Human Care Journal, 8(3), 481–495. https://doi.org/https://dx.doi.org/10.32883/hcj.v8i3.2634 Fatria, E., Priadi, A., Artanti, G. D., &; Alhamda, S. (2024). Utilizing the Geoeco-Book Learning Package to Improve Eco-Literacy of Z Generation Students in Elementary Schools. GeoEco, 10(1), 39–53. https://doi.org/https://doi.org/10.20961/ge.v10i1.82151 Fatria, E., Putrawan, I. M., &; Artanti, G. D. (2019). Environment and commitment, locus of control and intention to act. Indian Journal of Public Health Research and Development, 10(9), 1781–1785. https://doi.org/10.5958/0976-5506.2019.02711.6 Fatria, E., Rahmat Suwandi SN, F., &; Fadhani, M. (2023). Socialization of education in nursing to improve interpersonal intelligence for students. Empowering Society Journal, 4(2), 125–139. https://ojs.fdk.ac.id/index.php/ESJ/article/view/2597/pdf Firdausyi, A. N., Noormawanti, N., &; Marlisa, L. (2022). Implementation of naturalist intelligence in children in the learning theme